difference in the explanation of : Al-Mufassal in the section of the condition - المساعيد, ندوة (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
This study dealt with al-Zamakhshari’s book al-Mufassal, and three of the most important commentaries on it in the seventh century AH, namely: al-Khwarizmi’s commentary in 617 AH, Ibn Ya’ishi’s commentary in 643 AH, and Ibn al-Hajib’s commentary in 646 AH. There is a difference in this section, and the study came in four main axes related to the study of the conditional style: the first: the term, the second: the classification of tools, the third: the factor, and the fourth: provisions in the section of the condition and the sub-issues that fall under it; The study concluded that Ibn Ya'ish's commentary was the most detailed and familiar with grammatical issues, and his opinion was evident in every issue of the chapter.